Typification of the name Cleome turkmena (Cleomaceae) - Khorasani, Mina; Naqinezhad, Alireza; Iamonico, Duilio (Phytotaxa, 2024)
Cleome Linnaeus (1753: 671), in its traditional sense, is the largest genus of the family Cleomaceae Bercht. & Presl, comprising 200–300 species (Hall 2008, Patchell et al. 2014, Soares Neto et al. 2022, POWO 2024) which are native to the tropical, subtropical, and arid regions of both hemispheres (Patchell et al. 2014, Mousa 2019, Shilla et al. 2019, Roalson 2021, POWO 2024).